Serological and Molecular Diagnosis of Human Ehrlichiosis in Patients with Clinical Manifestations Associated with the Disease in Zulia, Venezuela, 2004-2005 - Mirtha Castro Morales; Francisco Arocha (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2012)
Human Ehrlichiosis is a zoonotic disease transmitted to humans through the bite of dog and occasionally, deer ticks. E. chaffeensis is the most common etiological agent related to human Ehrlichiosis; however, human Ehrlichiosis can be caused by canine ehrlichias such as E. canis and E. ewingii. In 1992, in the State of Zulia, the first case of human Ehrlichiosis appeared in a 17-month-old infant, in whom antibodies against E. chaffeensis were detected. The aim of this research was to study the presence of Ehrlichia spp. infection in the serum and whole blood of 30 persons with clinical symptoms associated with the disease. This was accomplished through techniques of indirect immunofluorescence and nested polymerase chain reaction assay (nested PCR), using primers derived from the genetic sequence that codify the ribosomal RNA 16S of Ehrlichia spp., which give information regarding gender but not species; due to this, gender primers are needed that could detect Ehrlichias in any host. None of the samples in the IFI assay was positive; no antibodies for Ehrilichia spp. were in evidence. The nested PCR test did not show amplification of the target sequence. The data did not support the evidence of Ehrlichia spp. infection in the patients studied.